Využití konceptů míst v antropologii a příbuzných vědách - Okénková, Věra (Lidé města, 2015)
In the last few decades of the 20th century, the social sciences and the humanities were influenced by an emergence of geographical terms – place and space. This change in the paradigm, known as the spatial turn, represents a very popular approach in contemporary history, sociology, philosophy and anthropology, as well. But does anthropological research sufficiently profit from the concepts of place and space? Focusing on place, this article shows that these concepts allow anthropology to analyse not only material, functional or symbolic meaning, but they also enable one to treat the overlaps to broader and more abstract research questions stemming from different subdisciplines. The aim of this article is not to give an exhaustive overview of all of the theories and publications pursuing the term space, but rather to provide a possible insight to this issue and to show how appropriate it can be for anthropological research.